2005
DOI: 10.1002/aoc.937
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry of tributyltin(IV) complexes and their larvicidal activity on mosquito larvae: crystal and molecular structure of polymeric (Bu3Sn[O2CC6H4{NN(C6H3-4-OH(C(H)NC6H4OCH3-4))}-o])n

Abstract: A series of tributyltin(IV) complexes of 2-[(E)-2-(3-formyl-4-hydroxyphenyl)-1-diazenyl]benzoic acid and 4-[((E)-1-{2-hydroxy-5-[(E)-2-(2-carboxyphenyl)-1-diazenyl]phenyl}methylidene)amino]aryls have been investigated by electrospray mass spectrometry (ESI-MS) and tandem mass spectrometry (MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…These tributyltin(IV) complexes have shown promise as larvicides [12,13]. In addition, the tributyltin(IV) complexes were investigated by electrospray ionization (ESI) mass spectrometry [13], which is considered to be the softest and most suitable ionization technique for the analysis of organotin compounds [14], including complex structures with molecular weights (M W s) over 1000 Da and high polarity.…”
Section: Introductionmentioning
confidence: 99%
“…These tributyltin(IV) complexes have shown promise as larvicides [12,13]. In addition, the tributyltin(IV) complexes were investigated by electrospray ionization (ESI) mass spectrometry [13], which is considered to be the softest and most suitable ionization technique for the analysis of organotin compounds [14], including complex structures with molecular weights (M W s) over 1000 Da and high polarity.…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of previous work on the toxicity studies on the second instar of Aedes aegypti and Anopheles stephensi mosquito larvae, 26,27 the present report details a study of the toxicity studies of free 5- stages. The preparation of L 1 HH (Fig.…”
Section: Introductionmentioning
confidence: 79%
“…Larvicidal effects of compounds A-C on Ae. aegypti mosquito larvae had also been better than triorganotin (IV) complex compound because compound A-C have higher LC 50 values (Baul et al, 2005). Organic group and ligand that attached to the tin atom were the main factor that influence the biological activity of organotin (IV) (Boraiko and Batt, 2005;Awang et al, 2010;Pellerito et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed organotin (IV) compounds were effective against some pests like periplanata Americana, musca domestica, Spodoptera litura and Tetranychus urticae (Shukla et al, 2010) and a few species of larvae and adult mosquitoes like Aedes Aegypti and Aenopheles stephensi (Eng et al, 2003;Baul et al, 2005;. Group and the nature of organic group that bound to tin atom, such as the monoalkyl, dialkyl and trphenyl are the basic factors determining the biological activity (Boraiko and Batt, 2005;Awang et al,2010;Pellerito et al, 2006).…”
Section: Introductionmentioning
confidence: 99%